On Typology of Free Time (I) - Mitrikas, Algimantas (Problemos, 1975)
The growing importance of free time in modern socialist society raises the necessity of revealing interrelations and interaction between various aspects of manifestations of processes in the sphere of free time and between free time and other spheres of human activity. One of the most important places in the research of these interrelations and interactions belongs to the exposure of complex “behaviour” of elements of the system of free time. This “behaviour” may be specified in certain types of spending free time. The peculiar type of spending free time is the style of free time which manifests itself as an organic structural part of the way of life in the socialist society. In disclosing styles of free time on the level of particular individuals one should avail oneself of such characteristics: 1) the structure of free time; 2) the degree of stability and regularity of the structural elements of free time; 3) contents of free time activity; 4) intensity of the activity. These should be supplemented by the characteristics expressing social-psychological condition of man at leisure: 1) the degree of free-will activity and behaviour; 2) the assessment of expediency and efficiency of the activity; 3) the degree of initiative and independence of the activity; 4) the character of “involvement” in this activity, etc.